2019
DOI: 10.1177/0142723719875575
|View full text |Cite
|
Sign up to set email alerts
|

Does children’s visual attention to specific objects affect their verb learning?

Abstract: To learn a verb, children must attend to objects and relations, often within a dynamic scene. Several studies show that comparing varied events linked to a verb helps children learn verbs, but there is also controversy in this area. This study asks whether children benefit from seeing variation across events as they learn a new verb, and uses an eye tracker to test whether children adjust their visual attention to specific objects to better understand how they may be comparing events to each other. Children sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…That study tested whether children benefited from seeing similar than varied events as opposed to all varied events and showed that children seeing those similar events first increased their looking to important elements in events (e.g., agents, affected objects), and by age 3, could succeed in extending the new verbs at test only in this similar first condition. They also add to the Childers et al 2020 [27] study which showed that children increased their visual attention to object types that varied across a learning set (tools and affected objects); this suggests children noticed which element varied likely because they were comparing elements across the events. Together, these studies [15,27] with the present result-showing greater attention to hands, and less attention to faces, only for relevant events-all show different ways children attend to specific elements of events as they learn verbs, which is important.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…That study tested whether children benefited from seeing similar than varied events as opposed to all varied events and showed that children seeing those similar events first increased their looking to important elements in events (e.g., agents, affected objects), and by age 3, could succeed in extending the new verbs at test only in this similar first condition. They also add to the Childers et al 2020 [27] study which showed that children increased their visual attention to object types that varied across a learning set (tools and affected objects); this suggests children noticed which element varied likely because they were comparing elements across the events. Together, these studies [15,27] with the present result-showing greater attention to hands, and less attention to faces, only for relevant events-all show different ways children attend to specific elements of events as they learn verbs, which is important.…”
Section: Discussionmentioning
confidence: 83%
“…They also add to the Childers et al 2020 [27] study which showed that children increased their visual attention to object types that varied across a learning set (tools and affected objects); this suggests children noticed which element varied likely because they were comparing elements across the events. Together, these studies [15,27] with the present result-showing greater attention to hands, and less attention to faces, only for relevant events-all show different ways children attend to specific elements of events as they learn verbs, which is important.…”
Section: Discussionmentioning
confidence: 83%
“…Therefore, it may be recommended and beneficial that both results from pointing and looking measures, and the proportion of absent pointing responses should be reported to interpret obtained data in more detail. In fact, some researchers conducted a similar task using both modalities as dependent variables and compared differences between them (Abbot- Smith et al, 2017;Childers, Porter, Dolan, Whitehead, & McIntyre, 2020;Gurteen et al, 2011;Hendrickson & Friend, 2013;Hendrickson et al, 2015Hendrickson et al, , 2017Suanda, Walton, Broesch, Kolkin, & Namy, 2013). Another practical strategy would be to estimate and interpolate missing pointing responses (i.e., left or right) from preferential looking, leveraging the findings that both manual and looking measurements have overlapping underlying information on toddlers' volitional choice and the former measures are substantially predicted from the latter ones regardless of the execution of pointing or reaching.…”
Section: Discussionmentioning
confidence: 99%
“…Two cameras were set to record toddlers' responses for later coding (30 frames/second): One was placed in an overhead position so that participants' entire body could be seen; the other (a webcam) was set at the center of the top of the screen so that participants' preferential looking could be recorded. The forced-choice task was conducted so that both pointing and looking responses could be obtained concurrently, as seen in previous studies (Childers, Porter, Dolan, Whitehead, & McIntyre, 2020;Hendrickson & Friend, 2013;Hendrickson, Mitsven, Poulin-Dubois, Zesiger, & Friend, 2015;Hendrickson, Poulin-Dubois, Zesiger, & Friend, 2017) because toddlers in our target age range often showed an absence of volitional pointing, which possibly increased missing data. The forced-choice task required approximately 10 minutes to complete.…”
Section: Apparatus and Proceduresmentioning
confidence: 99%
“…The visual display has its own charm for elementary and kindergarten pupils. The pupils tend to remember and even retain information about the objects they are interested in (Winarni, Hambali, and Purwandari, 2020;Childers, Porter, Dolan, Whitehead, and McIntyre, 2020;Wicks, Paynter, and Westerveld, 2020;Liu and Liu, 2020). This also happens when pupils are invited to visit the Geology Museum.…”
Section: Introductionmentioning
confidence: 99%